Rhabdomyosarcoma of the Maxilla - Karel Mercken; Maarten Steyvers; Robert Hermans (Journal of the Belgian Society of Radiology)
Rhabdomyosarcoma is the most common soft tissue sarcoma in children but is less frequent in adults, with the head and neck region as primary site. Magnetic resonance imaging (MRI) is the preferred diagnostic imaging tool, though its imaging characteristics are relatively non-specific and overlap with other soft tissue sarcomas. The prognosis of rhabdomyosarcoma depends on the primary tumour site and size, with parameningeal head and neck localisations having a less favourable prognosis due to the higher risk of spread. Therefore, further imaging including brain and spinal MRI is recommended. Teaching point: The prognosis of rhabdomyosarcoma depends on the primary tumour site and size, with parameningeal head and neck localisations having a less favourable prognosis due to the higher risk of spread.